Root cellaring : natural cold storage of fruits & vegetables - Bubel, Mike.; Bubel, Nancy (Pownal, VT : Storey Pub., 1991)
Anyone can learn to store fruits and vegetables safely and naturally with a cool, dark space (even a closet!) and the step-by-step advice in this book.
Includes bibliographical references (p. 283-286) and index.
Keywords: Vegetables -- Storage; Fruit -- Storage; Vegetable gardening; Root cellars; Food -- Storage